Deliberative Discussion Focus Groups. (May 2016) - Rothwell, Erin; Anderson, Rebecca; Botkin, Jeffrey R.
This article discusses a new approach for the conduct of focus groups in health research. Identifying ways to educate and inform participants about the topic of interest prior to the focus group discussion can promote more quality data from informed opinions. Data on this deliberative discussion approach are provided from research within three federally funded studies. As healthcare continues to improve from scientific and technological advancements, educating the research participants prior to data collection about these complexities is essential to gather quality data.